Implementation of Kalman Filter on PID Based Quadcopter for Controlling Pitch Angle - Dalimunthe, Ernando Rizki; Ananda, Novan Dwiki; Sembiring, Jaka Persada; Faidar, Muhammad Anwar Sadat; Pranita, Elka; Jayadi, Akhmad; Putri, Novia Utami (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2025)
Improving quadcopter control systems poses significant challenges in unmanned flight technology development. Key issues include the intricate nature of PID and Kalman filter parameter settings, necessitating profound knowledge of system dynamics and sensor properties. Furthermore, successfully integrating the Kalman Filter with PID control demands meticulous coordination to optimize state estimation precision and system responsiveness. This research emphasizes the incorporation of the Kalman filter into PID-based control for quadcopter pitch angle regulation. The Proportional-Integral-Derivative (PID) approach governs pitch angle, augmented by the Kalman Filter, to enhance estimation accuracy and mitigate sensor uncertainty. Optimal outcomes during system response testing were achieved with parameters of Kp at 2.95, Ki at 0.23, and Kd at 0.02, resulting in superior oscillatory response, including a 9-degree overshoot, a 5-second rise time, a 15-second settling time, and a 0.15-degree steady-state error, showcasing effective regulation of the quadcopter pitch angle. A concurrent observation during testing indicated that including the Kalman filter led to a significantly reduced overshoot compared to tests without it; conversely, the settling time experienced considerable acceleration, while measurement accuracy in the steady-state condition improved by 50%.